Zróżnicowanie doświadczeń rodzicielskich w grupie migrantów - Moritz-Leśniak, Wiktoria (Człowiek i Społeczeństwo, 2024)
In the face of the transformation of parenting and increased societal mobility, discussions about contemporary parenthood should pay attention to individuals with migration experience. The aim of the article is to review mainly Polish but also foreign research related to families having migration experience, with particular focus on parental experience. The topic will be presented from three perspectives: anthropology, sociology, and psychology, each highlighting different elements of these experiences. The article attempts to systematize research conducted by Polish researchers and theories related to specific aspects of migrant parents’ experience. Based on emergent categorization, the paper then proceeds with an analysis of mothers’ and fathers’ roles and their parenting practices.